2014
DOI: 10.1002/jor.22604
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shockwave increases the effectiveness of systemic antibiotic treatment in implant‐related chronic osteomyelitis: Experimental study in a rat model

Abstract: Implant-related chronic osteomyelitis is a serious complication of orthopedic surgery requiring implant removal and radical debridement. Extracorporeal shockwave (ESW) have demonstrated significant bactericidal effectiveness in vitro and effectiveness and safety were evaluated in an animal model of osteomyelitis. In this experimental study, we aimed to test our hypothesis that the use of ESW together with systemic antibiotic treatment will provide synergy for the treatment of implant-related chronic osteomyeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
8
0
3
Order By: Relevance
“…Wang et al (2014) reported that high-energy ESWs can exert favorable bactericidal effects if a suitable impulse rate is selected. Inanmaz et al (2014) reported that ESWs could be a valuable adjunct in the management of chronic implant-related osteomyelitis and that these waves acted in synergy with systemic antibiotic treatment; however, they concluded that further in vitro studies were required to determine the optimal treatment conditions. Horn et al (2009b) confirmed that ESWs can result in a significant reduction of CFUs when bacteria were treated in solution, but no in vivo study was conducted.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Wang et al (2014) reported that high-energy ESWs can exert favorable bactericidal effects if a suitable impulse rate is selected. Inanmaz et al (2014) reported that ESWs could be a valuable adjunct in the management of chronic implant-related osteomyelitis and that these waves acted in synergy with systemic antibiotic treatment; however, they concluded that further in vitro studies were required to determine the optimal treatment conditions. Horn et al (2009b) confirmed that ESWs can result in a significant reduction of CFUs when bacteria were treated in solution, but no in vivo study was conducted.…”
Section: Discussionmentioning
confidence: 96%
“…Various studies have been conducted that indicate that ESWs have bactericidal effects under appropriate conditions when combined with anti-biofilm therapy in vitro or in vivo (Horn et al 2009a;Inanmaz et al 2014). Wang et al (2014) reported that high-energy ESWs can exert favorable bactericidal effects if a suitable impulse rate is selected.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Серед ефектів ЕУХТ відзначають: сприяння неоваскуляризації внаслідок активації судинноендотеліального фактору росту з наступною пролі-ферацією ендотеліальних клітин [13,20]; індукцію остеогенетичних факторів росту, таких як трансформуючий фактор росту бета-1 та кісткових морфогенетичних білків, що ініціює активність остеобластів [13,19,21]; зниження больового синдрому [14,22]; зменшення набряку [23]. Відповідно до цього, низкою дослідників були сформульовані наступні показання до застосування ЕУХТ у щелепно-лицевій ділянці: лінійні переломи кісток, зокрема неконсолідовані [24,25]; пародонтит [20,26]; імплантація, зокрема лікування периімплантитів [27]; захворювання скронево-нижньощелепного суглоба [28].…”
Section: екстракорпоральна ударно-хвильова терапіяunclassified